2021
DOI: 10.1016/j.ejvs.2020.11.030
|View full text |Cite|
|
Sign up to set email alerts
|

Editor's Choice – A Cost Effectiveness Analysis of Outpatient versus Inpatient Hospitalisation for Lower Extremity Arterial Disease Endovascular Revascularisation in France: A Randomised Controlled Trial

Abstract: WHAT THIS PAPER ADDS AMBUVASC was the first cost effectiveness analysis associated with a prospective randomised controlled trial in France that compared outpatient vs. inpatient hospitalisation for the endovascular repair of lower extremity arterial disease (LEAD). From a societal perspective, considering a one month time horizon, outpatient hospitalisation was not cost effective compared with inpatient hospitalisation for a V50 000 per quality adjusted life year (QALY) threshold (the incremental cost effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In France, outpatient surgery units remain under the administrative control of hospitals and no financial incentive was given before 2019 to promote outpatient endovascular surgery. Nevertheless, we excluded high-risk patients using medical criteria similar to those of other studies [8,11,19,27] (i.e. the American Society of Anesthesiology score and recent guidelines [28]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In France, outpatient surgery units remain under the administrative control of hospitals and no financial incentive was given before 2019 to promote outpatient endovascular surgery. Nevertheless, we excluded high-risk patients using medical criteria similar to those of other studies [8,11,19,27] (i.e. the American Society of Anesthesiology score and recent guidelines [28]).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that procedural and postoperative complications of endovascular revascularization within 30 days of surgery occur in 10% to 13% of the patients [15,16]. In addition, outpatient endovascular repair for LEAD does not seem to increase the risk of complications and hospital readmission [8,[16][17][18]; however, the AMBUVASC randomized clinical trial (RCT) showed more readmissions in the outpatient than in the inpatient arm [19].…”
Section: Introductionmentioning
confidence: 99%
“…11,32,33 Second, the cost effictiveness of ambulatory endovascular revasculatisation remains a question. For instance, The AMBUVASC randomised control trial showed that on one month time horizon, ambulatory interventions was not cost effective compared with conventional hospitalisation for a €50 000 per quality adjusted life year threshold 7 . The authors reported that this result was mainly explained by the higher number of re-admissions in the outpatient arm.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…For more than a decade, technological developments and the expertise of vascular teams have improved the management of LEAD, offering endovascular treaments and outpatient hospitalisation. Although the benefits of outpatients hospitalisations are still debated, notably about the complication rates or the burden of premature discharge on primary health care services [6][7][8][9] , several studies had demonstrated both increased resource efficiency and hospital cost savings, thanks to ambulatory endovascular treatments, while preserving patient safety [10][11][12][13] . Consequently, the development of endovascular interventions in ambulatory setting has accelerated significantly, mainly in the United States 14,15 .…”
Section: Introductionmentioning
confidence: 99%